Altruism, Human Capital and Environmental Preservation in a Globalized Economy - Stéphane Bouché; Leonor Modesto (Institute of Labor Economics (IZA), 2024)
This paper analyzes the impact of trade openness on education and environmental preservation choices in a two country model where both countries only differ in their shares of skilled workers. Parents may invest in their children's education increasing their probability to become skilled and in maintenance investment in order to preserve present and future environmental quality. Under autarky, unskilled individuals in the skill scarce economy are unable to invest in education due to borrowing constraints. Moreover, only skilled individuals of the latter economy choose to invest in environmental preservation. Openness to trade modifies relative factor prices and increases pollution. This allows for human capital convergence between both economies and induces all skilled individuals to contribute to environmental preservation in the free trade equilibrium. However, overall environmental quality decreases, suggesting a potential trade-off between income convergence at the global level and environmental preservation. We also focus on the optimal allocation under free trade and conclude that a maintenance investment subsidy should be implemented for skilled individuals but not necessarily for unskilled ones.
Keywords: D64; F18; F64; I25; 330; altruism; environmental preservation; international trade; human capital